A Musical 'Picture-Postcard Image' of Ireland: Michael W. Balfe's 'Killarney' (Journal of the Society for Musicology in Ireland, 2026)
At the end of the 19th century Michael William Balfe’s song ‘Killarney’ was extraordinarily popular in the English-speaking world. However, its status as an ‘Irish’ song was highly disputed. With its verbal and musical depiction of the idealized Irish landscape around the small town in County Kerry for some of its listeners it symbolized Irishness as its best. For others, it was just another drawing-room song of the Victorian age without any real reference to Ireland except for the Irish descent of its author.In this article the history and reception of ‘Killarney’ up to the beginning of the 20th century is researched thoroughly. In doing so a type of source that has hitherto been widely neglected by musicologists is taken into account: the picture postcard. As is shown by postcards with visualizations of the song, it was not only the lyrics and music of ‘Killarney’ that could evoke impressions of Ireland and Irishness. Moreover, the song referred to visual associations that had been popularized since the beginning of English tourism in Ireland in the 18th century.